2010
DOI: 10.1111/j.2042-7158.2010.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-glutamylcysteine ethylester on the levels of c-fos mRNA expression, glutathione and reactive oxygen species formation in kainic acid excitotoxicity

Abstract: The increased levels of glutathione and the reduced levels of reactive oxygen species formation lead us to conclude that GCEE may be beneficial as a potential antioxidant against neurodegenerative processes where excitotoxicity is involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Brain cells are particularly vulnerable to oxidative stress because of their high oxygen consumption, high content of unsaturated fatty acids and iron and decreased activities of antioxidant enzymes. Thus, effective antioxidant defence is vital for neuroprotection in the brain . Our previous study showed that intrahippocampal A β (1–42) injection caused significant increases in oxidative stress markers, and NA treatments provided a protection supporting antioxidant defence against the elevation of lipid peroxidation, protein oxidation and ROS production induced by A β (1–42) in vivo .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Brain cells are particularly vulnerable to oxidative stress because of their high oxygen consumption, high content of unsaturated fatty acids and iron and decreased activities of antioxidant enzymes. Thus, effective antioxidant defence is vital for neuroprotection in the brain . Our previous study showed that intrahippocampal A β (1–42) injection caused significant increases in oxidative stress markers, and NA treatments provided a protection supporting antioxidant defence against the elevation of lipid peroxidation, protein oxidation and ROS production induced by A β (1–42) in vivo .…”
Section: Discussionmentioning
confidence: 61%
“…Thus, effective antioxidant defence is vital for neuroprotection in the brain. [45][46][47][48] Our previous study showed that intrahippocampal A(1-42) injection caused significant increases in oxidative stress markers, and NA treatments provided a protection supporting antioxidant defence against the elevation of lipid peroxidation, protein oxidation and ROS production induced by A in vivo. 49 This study reveals the effects of A(1-42) on oxidative stress and mitochondrial reduction capacity and whether there are possible neuroprotective effects of 3-AB and NA in synaptosomes with an ex vivo experimental approach because the changes in these parameters might be relevant to synaptic loss that has been proposed as an early event in AD neuropathogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Since GCEE has been proven to be effective in vivo at doses of 10 mg/kg [25] and 150 mg/kg b.wt. [21], we selected a dose of 100 mg/kg to be tested in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, i.p. injections of GCEE protected against kainic acid induced ROS and downregulated c-fos mRNA in the cortex and hippocampus of rats [85]. GCEE may react directly with ROS due to the cysteine residue and/or increase GSH, which can protect against ROS and nucleophilic compounds.…”
Section: γ-Glutamylcysteine Ethyl Ester (Gcee)mentioning
confidence: 99%